Waterhouse friderichsen syndrome in a case of staphylococcal toxic shock syndrome - Devdeep Mukherjee; Prabhas Prasun Giri; Suman Poddar (Wolters Kluwer Medknow Publications, 2016)
Staphylococcal toxic shock syndrome (TSS) is a rare and potentially fatal multi system dysfunction. The syndrome occurs primarily due to TSS Toxin-1 (TSS-1) liberated by Staphylococcus aureus (SA). Fever with rash followed by multi organ dysfunction in the form of acute kidney injury, raised liver transaminases and refractory hypotension indicates the possible diagnosis of a TSS, more commonly by Staphylococcus. Here, a 7 year old boy presented with all the features of toxic shock syndrome, developed hyponatremia, hyperkalemia, refractory hypoglycaemia and hypotension and succumbed within 12 hours of admission and ultimately was diagnosed to be a case of Staphylococcal toxic shock syndrome due to MSSA with Waterhouse Friderichsen Syndrome (WFS).